Canonical Wnt signaling regulates Nkx3.1 expression and luminal epithelial differentiation during prostate organogenesis. Issue 10 (29th July 2013) - Kruithof‐de Julio, Marianna; Shibata, Maho; Desai, Nishita; Reynon, Melissa; Halili, M. Vivienne; Hu, Ya‐Ping; Price, Sandy M.; Abate‐Shen, Cory; Shen, Michael M.
<x xml:space="preserve">Abstract</x> Background: The formation of the prostate gland requires reciprocal interactions between the epithelial and mesenchymal components of the embryonic urogenital sinus. However, the identity of the signaling factors that mediate these interactions is largely unknown. Results: Our studies show that expression of the prostate‐specific transcription factor Nkx3.1 is regulated by the canonical Wnt signaling pathway. Using mice carrying a targeted lacZ knock‐in allele of Nkx3.1, we find that Nkx3.1 is expressed in all epithelial cells of ductal buds during prostate organogenesis. Addition of Wnt inhibitors to urogenital sinus explant culture greatly reduces prostate budding and inhibits Nkx3.1 expression as well as differentiation of luminal epithelial cells. Analyses of a TCF/Lef:H2B‐GFP transgene reporter show that canonical Wnt signaling activity is found in urogenital mesenchyme but not urogenital sinus epithelium before prostate formation, and is later observed in the mesenchyme and epithelium of prostate ductal tips. Furthermore, TCF/Lef:H2B‐GFP reporter activity is reduced in epithelial cells of Nkx3.1 null neonatal prostates, suggesting that Nkx3.1 functions to maintain canonical Wnt signaling activity in developing prostate bud tips. Conclusions: We propose that activated canonical Wnt signals and Nkx3.1 function in a positive feedback loop to regulate prostate bud growth and luminal epithelial differentiation. Developmental Dynamics, 242:1160–1171, 2013. © 2013 Wiley Periodicals, Inc.